Konsep Industrialisasi dan Transformasi Struktural di Indonesia - Rifdatul Hanifah; Muhammad Yasin (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
Regional economic development is closely related to changes and transformations of economic structures. There are four main aspects of economic development, namely growth, poverty alleviation, economic transformation, and sustainable development from an agrarian to industrial society. In Indonesia, economic development has encouraged growth and changes in economic structure, which are closely related. Structural transformation, namely the transition from the agricultural sector to the industrial or service sector, is a characteristic feature of developing countries. It involves changes in demand, trade, production, and other factors aimed at increasing per capita income and societal welfare. State-controlled industrialization policies have intellectual roots in the 19th century and have been the main strategy in many developing countries, including Indonesia since 1969. This strategy succeeded in shifting the economic focus from the agricultural sector to the industrial and service sectors, which also involved social transformation in addition to transformation. economy. Industrialization is defined as a significant socio-economic change, from a pre-industrial stage with low per capita income to a more advanced industrial stage.